2021
DOI: 10.3389/fnmol.2021.711396
|View full text |Cite
|
Sign up to set email alerts
|

Severe and Regionally Widespread Increases in Tissue Urea in the Human Brain Represent a Novel Finding of Pathogenic Potential in Parkinson’s Disease Dementia

Abstract: Widespread elevations in brain urea have, in recent years, been reported in certain types of age-related dementia, notably Alzheimer’s disease (AD) and Huntington’s disease (HD). Urea increases in these diseases are substantive, and approximate in magnitude to levels present in uraemic encephalopathy. In AD and HD, elevated urea levels are widespread, and not only in regions heavily affected by neurodegeneration. However, measurements of brain urea have not hitherto been reported in Parkinson’s disease dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…Urea being a nitrogenous base of protein metabolism, its increase in the brains of PD patients has been subjected to much debate, especially in conditions where blood urea remained normal. The blood-brain barrier (BBB) is impermeable to urea; hence, increased brain urea levels in the present study indicate either increased synthesis of brain urea inside the central nervous system or breakage of BBB 54 . A similar experimental study on PD also suggests increased brain urea in Wistar rats induced with rotenone 37 .…”
Section: Urea Changes In Thementioning
confidence: 72%
“…Urea being a nitrogenous base of protein metabolism, its increase in the brains of PD patients has been subjected to much debate, especially in conditions where blood urea remained normal. The blood-brain barrier (BBB) is impermeable to urea; hence, increased brain urea levels in the present study indicate either increased synthesis of brain urea inside the central nervous system or breakage of BBB 54 . A similar experimental study on PD also suggests increased brain urea in Wistar rats induced with rotenone 37 .…”
Section: Urea Changes In Thementioning
confidence: 72%
“…In recent years, diffused elevations in brain urea have been reported in certain types of age-related neurodegenerative diseases, i.e., Alzheimer's disease (AD), 53 Huntington's disease (HD) 54,55 and Parkinson disease (PD). 56 Urea cycle activity localizes primarily in the liver, but systemic over-production of urea is not known in AD and HD. These findings have been correlated to impaired local urea regulation in brain, by up-regulation of synthesis and/or defective clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, urea was significantly upregulated in urine samples from injury groups compared to the control group. Urea is substantial nitrogen- (N-) containing end product of protein metabolism, having a critical effect on excreting dangerous N-containing substances [ 19 , 20 ]. Ammonia will be transformed into urea during the urea cycle, while urea is later discharged through urine out of the body [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the excess released glutamate is reduced through the urea cycle and shortens the tricarboxylic acid cycle-induced glutamate oxidation [ 24 ]. Furthermore, previous research showed that brain urea played a pivotal role in neurodegenerative diseases and was significantly increased in Parkinson's disease dementia (PDD), Huntington's disease (HD), and Alzheimer's disease (AD) [ 20 ]. During DAI, the upregulated urea in urine could be an endogenous protective mechanism to reduce subsequent axonal damage postinjury.…”
Section: Discussionmentioning
confidence: 99%